Innovation, Organisational Learning and Knowledge Management in Educational Organisations - Rodríguez-Gómez, David (2015)
Educational organisations call for strategies that allow them to meet the constant and changing demands of their environment. It is not a question of organisations adapting to social change, but of them also being able to anticipate change and to seek out alternatives. It is precisely the development of organisational learning and knowledge management strategies that allows these challenges to be met, providing organisations with tools and processes that allow them to generate new knowledge and capitalise on existing knowledge, thereby improving staff performance and, therefore, the performance of the organisation itself. In this paper, do we examine the development of organisational learning processes in educational institutions, and we also advocate knowledge management as the best strategy for promoting organisational learning and innovation.